2012
DOI: 10.5624/isd.2012.42.4.243
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of simulated periodontal bone defects in inverted digital image and film-based radiograph: an in vitro study

Abstract: PurposeThis study was performed to compare the inverted digital images and film-based images of dry pig mandibles to measure the periodontal bone defect depth.Materials and MethodsForty 2-wall bone defects were made in the proximal region of the premolar in the dry pig mandibles. The digital and conventional radiographs were taken using a Schick sensor and Kodak F-speed intraoral film. Image manipulation (inversion) was performed using Adobe Photoshop 7.0 software. Four trained examiners made all of the radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…1 In those studies, soft-tissue simulators are often used to simulate what is present in vivo. 2 In a clinical situation, when an X-ray beam interacts with soft tissues and reaches the object, its intensity is attenuated, resulting in low-energy photons producing low-density areas in the image.…”
Section: Introductionmentioning
confidence: 99%
“…1 In those studies, soft-tissue simulators are often used to simulate what is present in vivo. 2 In a clinical situation, when an X-ray beam interacts with soft tissues and reaches the object, its intensity is attenuated, resulting in low-energy photons producing low-density areas in the image.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 All periapical radiographs of the inserted implants were evaluated for proximal bone loss between the two groups and among periods. The distance from the implant shoulder on the mesial and distal aspects to the alveolar bone crest was measured for each implant.…”
Section: Radiographic Examinationmentioning
confidence: 99%
“…The diagnostic performance of two dimensional digital imaging systems was found to be comparable with conventional radiography. Studies reported the usefulness of digital imaging in caries diagnosis [4][5][6], periodontal bone defects [7][8][9], endodontic applications and diagnosis of periapical lesions [10,11], root fractures [12] and root resorption [13,14].…”
Section: Two Dimensional Digital Imaging In Dentistrymentioning
confidence: 99%